PEMBERSIHAN DAN PENATAAN DESA MELALUI KEGIATAN KULIAH KERJA NYATA (KKN) DI DESA DUMA KECAMATAN GALELA BARAT - Olivia Akerina, Febrina; Kour, Femsy; Wangehela, Ramon; Dobiki, Herawati (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
The environment is something that is closely related to human life, which means that humans naturally interact with the environment. A clean and comfortable environment can also be achieved through environmental planning activities. problems in managing environmental cleanliness, and arranging nameplates for village officials as well as other problems related to the environment that must be resolved. This activity aims to organize the village by making nameplates for village officials and overcoming environmental cleanliness management problems. Activities carried out include cleaning the village environment, making rubbish bins, making and arranging village nameplates. The results of the activity evaluation show that all activities run well in accordance with the planned targets.